Literary Criticism : An Autopsy - Bauerlein, Mark (Book collections on Project MUSE., 1997)
As the study of literature has extended to cultural contexts, critics have developed a language all their own. Yet, argues Mark Bauerlein, scholars of literature today are so unskilled in pertinent sociohistorical methods that they compensate by adopting cliches and catchphrases that serve as substitutes for information and logic. Thus by labeling a set of ideas an "ideology" they avoid specifying those ideas, or by saying that someone "essentializes" a concept they convey the air of decisive refutation. As long as a paper is generously sprinkled with the right words, clarification is deemed superfluous. Bauerlein contends that such usages only serve to signal political commitments, prove membership in subgroups, or appeal to editors and tenure committees, and that current textual practices are inadequate to the study of culture and politics they presume to undertake. His book discusses 23 commonly encountered terms--from "deconstruction" and "gender" to "problematize" and "rethink"--And offers a diagnosis of contemporary criticism through their analysis. He examines the motives behind their usage and the circumstances under which they arose and tells why they continue to flourish. A self-styled "handbook of counterdisciplinary usage," Literary Criticism: An Autopsy shows how the use of illogical, unsound, or inconsistent terms has brought about a breakdown in disciplinary focus. It is an insightful and entertaining work that challenges scholars to reconsider their choice of words--and to eliminate many from critical inquiry altogether